Exploring the impact, response and preparedness to water-related natural disasters in the Barisal division of Bangladesh: a mixed methods study. Issue 4 (4th April 2019) - Jagnoor, Jagnoor; Rahman, Aminur; Cullen, Patricia; Chowdhury, Fazlul Kader; Lukaszyk, Caroline; Baset, Kamran ul; Ivers, Rebecca
Abstract : Objectives: To investigate the impact of natural disasters on communities in the Barisal division of Bangladesh, exploring community approaches to disaster preparedness and mitigation. Setting: Communities in all districts of the Barisal division of Bangladesh. Participants: Quantitative data were collected through a cross-sectional household survey (n=9263 households; n=38 981 individuals). Qualitative data were collected through in-depth interviews (n=7) and focus group discussions (n=23) with key informants. Outcome measures: Quantitative research recorded features of natural disaster events from the previous 5 years, documenting risk factors that increase vulnerability to disaster, use of disaster warning systems and evacuation processes. Qualitative research investigated disaster risk perceptions, experiences during and following disaster, and disaster preparedness practices. Results: The survey response rate was 94.7%. Exposure to disaster in the last 5 years was high (82%) with flooding and cyclones considered the greatest threats. Awareness of evacuation processes was low; and only 19% of respondents evacuated their homes at the time of disaster. Drowning during disaster was the primary concern (87%), followed by debt, livestock and crop loss (78%). The qualitative findings indicated prevailing fatalistic perceptions towards natural disasters among community. The consequences of disasters included significant loss of livelihoods and exposure to infections due to poor sanitation. There was also insufficient support for the most vulnerable, particularly women, children and the elderly. Although several community preparedness and practices existed, there was a lack of response to early warning systems. Barriers to disaster response and resilience included financial insecurities, loss of livelihoods and cultural concerns regarding women's privacy. Conclusions: Critical to achieving disaster resilience is increased government investment in infrastructure and systems-level responses that empower communities. Further research can support this by addressing community challenges to promoting disaster resilience and how to leverage existing community strengths to implement locally owned solutions.